Fitness determinants of repeated high-intensity effort ability in elite rugby union players - Vachon, A.; Berryman, N.; Mujika, I.; Paquet, J. B.; Bosquet, L. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To investigate the relationship between physical fitness and repeated high-intensity effort (RHIE) ability in elite rugby union players, depending on playing position.